Microplastics: Global occurrence, impact, characteristics and sorting - Prabhu, Prathiksha P.; Pan, Koustav; Krishnan, Jegatha Nambi (Frontiers in Marine Science, 2022)
Stressors like microplastics (MPs) cause proliferating environmental pollution globally. Since plastics are continuously introduced into water bodies through numerous paths, novel solutions are required to segregate as well as decline their quantity in various environmental sectors. Numerous techniques have been used and proposed in the last ten years to screen and enumerate MPs, define the particle's properties, for instance form, color or size, and recognize the polymer material. This critical review aims to provide an overview of advanced procedures in MP investigation, provides illustrations of probable routes forward and lingering challenges, plus categorizes present approaches as per their underlying research question. Methods presently employed for MP sampling, extraction, identification, characterization, and quantification were evaluated. Studies proposing use of precursors for removal of MPs from water via sol-gel process were reviewed. Research on microfluidics systems finds application in environmental and industrial fields and have gained momentum in concentrating, sorting, classifying, focusing and desegregating MPs. This review briefly discusses active and passive label-free microfluidic methods that are efficient in executing the desired particle separation and are gaining momentum in the ecological analysis of MPs. Although some sets of preliminary data of MPs at selected regions across the globe have been studied and obtained. Degree of MP contamination in most important rivers, near shore inland areas, and air is yet to be understood completely. Along Charleston Harbour Estuary, MP concentration in intertidal sediment was found to be 0 to 652 microplastics/m2. In Asia, at the South Korean region, western Pacific Ocean, high plastic concentrations 15– 9,400 particles/m3 was reported. In India, MP concentration was identified as 288 pieces/m3 in the Nethravathi river. In Turkey, ingestion of MPs was reported to be found in 458 out of 1337 fish samples, indicating the polluted situation of Mediterranean Sea. Despite the rapid development in MPs analysis, no standardized technique for sampling along with separation has been approved. Therefore, for attaining a more inclusive picture of MPs fate and abundance, this study highlights the importance of a standardized procedure for MP research that can be used globally and adequately enables comparisons around the world.